The WNT/β-catenin pathway is involved in the anti-adipogenic activity of cerebrosides from the sea cucumber Cucumaria frondosa. Issue 7 (8th July 2015) - Xu, Hui; Wang, Fei; Wang, Jingfeng; Xu, Jie; Wang, Yuming; Xue, Changhu
<x xml:space="preserve">Abstract</x> Both adipocyte hypertrophy and hyperplasia lead to obesity.